Thermal evolution of hybrid stars within the framework of a nonlocal Nambu-Jona-Lasinio model - de Carvalho, S. M. (2015)
We study the thermal evolution of neutron stars containing deconfined quark matter in their core. Such objects are generally referred to as quark-hybrid stars. The confined hadronic matter in their core is described in the framework of nonlinear relativistic nuclear field theory. For the quark phase we use a nonlocal extension of the SU(3) Nambu-Jona-Lasinio model with vector interactions. The Gibbs condition is used to model phase equilibrium between confined hadronic matter and deconfined quark matter. Our study indicates that high-mass neutron stars may contain between 35 and 40% deconfined quark-hybrid matter in their cores. Neutron stars with canonical masses of around 1.4M⊙ would not contain deconfined quark matter. The central proton fractions of the stars are found to be high, enabling them to cool rapidly. Very good agreement with the temperature evolution established for the neutron star in Cassiopeia A (Cas A) is obtained for one of our models (based on the popular NL3 nuclear parametrization), if the protons in the core of our stellar models are strongly paired, the repulsion among the quarks is mildly repulsive, and the mass of Cas A has a canonical value of 1.4M⊙.